1989
DOI: 10.1007/bf00003872
|View full text |Cite
|
Sign up to set email alerts
|

Tissue culture of Ecklonia radiata (Phaeophyceae, Laminariales): effects on growth of light, organic carbon source and vitamins

Abstract: The effects of light quality and irradiance, and supply of organic carbon and vitamins on the growth of two forms of Ecklonia radiata in tissue culture were examined. A callus of unpigmented cells developed over the cut surface of newly excised explants of stipe. This growth was best in the dark but stopped after 10 weeks. Pigmented, mainly filamentous clumps of cells developed from explants after several weeks in culture. These required light for growth, with growth being enhanced by increasing photon flux de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
1

Year Published

1991
1991
1995
1995

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 26 publications
0
22
1
Order By: Relevance
“…The use of glycerol in combination with phytohormones induced growth for more than 12 months. Lawlor et al (1989) found a small stimulation of growth of Ecklonia radiata (Phaeophyta) in media supplemented with 1 mM or 10 mM glycerol.…”
Section: Resultsmentioning
confidence: 99%
“…The use of glycerol in combination with phytohormones induced growth for more than 12 months. Lawlor et al (1989) found a small stimulation of growth of Ecklonia radiata (Phaeophyta) in media supplemented with 1 mM or 10 mM glycerol.…”
Section: Resultsmentioning
confidence: 99%
“…to increase low growth rates (indicating suboptimal conditions) of seaweed tissue (Fries, 1973; and callus cultures (Nakamura, 1974;Saga & Sakai, 1983) has resulted in both stimulatory effects and no effects (Robaina, 1988;Lawlor etal., 1988). Nutrient depletion could be the reason for callus and 'callus-like' inductions or reversions (PedersCn, 1968;Fries, 1980;Bradley & Cheney, 1986;Lawlor et al, 1989). Sugars have been reported to be unnecessary or even inhibitory to tissue (Fucus spiralis: Fries, 1984), callus (Ecklonia radiata: Lawlor et al, 1989) and cell culture (Porphyra umbilicalis: Tait et al, 1990) growth or organogenesis.…”
Section: Culture Mediamentioning
confidence: 99%
“…Nutrient depletion could be the reason for callus and 'callus-like' inductions or reversions (PedersCn, 1968;Fries, 1980;Bradley & Cheney, 1986;Lawlor et al, 1989). Sugars have been reported to be unnecessary or even inhibitory to tissue (Fucus spiralis: Fries, 1984), callus (Ecklonia radiata: Lawlor et al, 1989) and cell culture (Porphyra umbilicalis: Tait et al, 1990) growth or organogenesis. Our studies on the interrelationship between the osmolality of the culture medium and the effect of osmotically active sugar supplementation has shown that, as in higher plants (van Rensburg & Vcelar, 1989), the effects of carbohydrates in seaweed tissue and callus culture seem osmotic or metabolic or both (Robaina et al, 1990a;1990b).…”
Section: Culture Mediamentioning
confidence: 99%
See 2 more Smart Citations